2017
DOI: 10.1061/(asce)be.1943-5592.0001081
|View full text |Cite
|
Sign up to set email alerts
|

WIM-Based Live-Load Model for Advanced Analysis of Simply Supported Short- and Medium-Span Highway Bridges

Abstract: 4The accuracy of bridge system safety evaluations and reliability assessments obtained through refined structural 5 analysis procedures depends on the proper modeling of traffic load effects. While the live load models specified in the 6 AASHTO procedures were calibrated for use in combination with the approximate analysis methods and load distribution 7 factors commonly used in the U.S., these existing models may not produce accurate results when used in association with 8 advanced finite element analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In Oregon, truck WIM data were also used to develop state-specific LRFR live load factors, and the factors were calibrated using the same statistical methods that were used in the original development of LRFR [6]. Recently, Eamon et al conducted a reliability-based calibration of live load factors for bridge design specific to the state of Michigan, and it was found that Michigan load effects were greater than those previously assumed, requiring higher load factors than those in current use [7]; Rasheed et al implemented a structural reliability analysis of superstructure of highway bridges on the China-Pakistan Economic Corridor [8]; Oudah et al calibrated live load factors for bridge systems conveying extremely heavy mining trucks [9]; Anitori et al proposed a WIM-based live load model for advanced analysis of simply supported shortand medium-span highway bridges [10], and Siavashi and Eamon developed traffic live load models for bridge superstructure rating [11]. Besides, some efforts have been made to enhance the accuracy of load effect projections to longer period of time needed for design and rating [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In Oregon, truck WIM data were also used to develop state-specific LRFR live load factors, and the factors were calibrated using the same statistical methods that were used in the original development of LRFR [6]. Recently, Eamon et al conducted a reliability-based calibration of live load factors for bridge design specific to the state of Michigan, and it was found that Michigan load effects were greater than those previously assumed, requiring higher load factors than those in current use [7]; Rasheed et al implemented a structural reliability analysis of superstructure of highway bridges on the China-Pakistan Economic Corridor [8]; Oudah et al calibrated live load factors for bridge systems conveying extremely heavy mining trucks [9]; Anitori et al proposed a WIM-based live load model for advanced analysis of simply supported shortand medium-span highway bridges [10], and Siavashi and Eamon developed traffic live load models for bridge superstructure rating [11]. Besides, some efforts have been made to enhance the accuracy of load effect projections to longer period of time needed for design and rating [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The results presented in this paper are based on the traffic data from only one specific WIM station. The same methodology can be applied to a set of WIM stations in a specific region, state or country to develop specific amplification factors and live-load models, as presented in Anitori et al (2017). Furthermore, the calibration process provides information on site-to-site variability to calibrate different models for different traffic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proposed approach may in many cases lead to saving some bridges that may not traditionally rate well from immediate replacement or rehabilitation and may lead to a more efficient allocation of the limited resources currently available for managing our ageing bridge infrastructure. Additional work to extend the procedure proposed in this paper to cover different sets of WIM data and for the analysis of moment and shear effects on a wider range of bridge configurations is described by Anitori et al (2017).…”
Section: 2example 2: Rating Of a Deteriorated Bridgementioning
confidence: 99%
See 2 more Smart Citations